PECULIARITIES OF ACUTE RESPIRATORY DISEASES IN PATIENTS WITH ATOPY - L. O. Ponezheva; Zh. B. Ponezheva; A. N. Kupchenko (SINAPS LLC, 2015)
In the work identified clinical and immunological characteristics of the course of ARVI patients with atopy and assessed the clinical efficacy of transfer factor in patients with severe immune deficiency. Emphasized the role of respiratory infections as the most important triggers of exacerbations of atopy and causes more severe and prolonged course. Describes the mechanisms of how respiratory viruses potentiate chronic inflammation and remodeling of the airways. The role of the causative agents of ARVI in patients with atopy deserve more practical attention towards and optimization of therapy.